Literature Review 2020–2025: Inquiry Approach in E-Worksheets to Improve Elementary Students’ Critical Thinking Skills - Mandala, Dewa Duta; Wagiran, Wagiran; Widiyatmoko, Arif; Subali, Bambang (FKIP - Universitas Riau, 2026)
In 21st-century learning, students are required to possess critical thinking, communication, collaboration, and creative thinking competencies. From observations in the classroom, students often experience difficulties in understanding learning materials due to the use of conventional student worksheets, which have a declining impact on learning outcomes. This study aims to analyze the research trends in inquiry approaches in electronic worksheets to enhance critical thinking skills from 2020 to 2025. The method used is a systematic literature review, incorporating the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The analysis was conducted using content analysis and bibliometrics, employing VOSviewer for network visualization, overlay, and density review. The results of the review indicate that the inquiry approach in electronic worksheets has a significant impact on enhancing the critical thinking skills of elementary school students. This research provides a theoretical foundation for digital learning media developers, practical guidance for teachers, and contributes to improving the quality of basic education in the digital era.